Pengaruh Permainan Building Block terhadap Kecerdasan Visual Anak di TK Ulil Albab Kota Bandung - Ira Hastuti; Anita Santia (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2018)
The purpose of research is to determine the effect of building block games on visual intelligence early childhood in kindergarten Ulil Albab Bandung. The game building block is a constructive game where early childhood can develop their creative skills and imagination in making a building of various forms of lego. The research problem is how the influence of building block game to visual intelligence of early child in kindergarten Ulil Albab Bandung. The research method used is experimental research method. The type of experimental research that researchers use is one-group pretest posttest design. The results showed that with game building block significantly influence in stimulating visual intelligence of early child in kindergarten Ulil Albab Bandung. The result is based on t test with significance level α = 0,05 and dk = 12, where t count value t table, that is 17, 46 11,7 where H0 is rejected and H1 accepted. That is, the game building block significantly influence in stimulating visual intelligence early childhood in kindergarten Ulil Albab Bandung.